The big break : the gamblers, party animals & true believers trying to win in Washington while America loses its mind - Terris, Ben (Twelve, 2023)
"In this fascinating investigation into the real life inner workings of a post-Trump American government, uncover the odd and eccentric personalities grappling for their own bit of power in D.C. The Big Break investigates how Washington works, and how different kinds of people try to make it work for them. Ben Terris presents an inside history of this crucial moment in Washington, reporting from exclusive parties, poker nights, fundraisers, secluded farms outside town and the halls of Congress; among the oddballs and opportunists and true believers. This book is about the people who see this moment as an opportunity to bet big--on their country or maybe just on themselves. It will take a close look at Washington's bold-faced names as they try to get their bearings on the post-Trump (and possibly pre-Trump) landscape. And it will introduce readers to the behind-the-scenes players--MAGA pilgrims and Resistance flamekeepers and shapeshifting veterans--who believe they know what Washington, and America, must do if they're going to survive, or even thrive. Trump's arrival in Washington represented a big break in how the city operated. He surrounded himself with outsiders; power structures reorganized around those who knew him or his family and those who could flatter and influence his base. He changed the way the game was played, only it wasn't actually a game at all. When pro-Trump elements both inside and outside of government plotted to overturn his loss in the 2020 presidential election, the Capitol became a combat zone, then a military fortress. It was, to put it lightly, a destabilizing time. But how much did the Trump years really change Washington? Has Joe Biden's presidency heralded a return to normal, as many had hoped? What did 'normal' mean before Trump, and what do people think it means now? The Big Break will follow a cast of D.C. characters in search of answers to these questions. They are a diverse crew--a pollster with a gambling habit, an oil heiress with a big heart, a cowboy lobbyist, a Republican kingmaker who decided to love Trump and his right-hand man who decided he couldn't any longer. They all share at least one thing in common: They had seen their country go through a Big Break, and they'd come to get theirs"--